Quality Characteristics of Smoked Barracuda Fish (Sphyraena jello) Processed with Different Concentrations of Corncob Liquid Smoke - Fronthea Swastawati; Ulfa Nur Wahidah; Romadhon Romadhon (Jurnal Perikanan Universitas Gadjah Mada, 2022)
Smoking with liquid smoke is one of the alternative processing methods with lower temperatures and is expected to reduce protein and amino acid damage. This study aimed to determine the effect of different concentrations of corncob liquid smoke on the quality of both chemical and sensory of smoked barracuda fish. The method used was smoking barracuda fish with four different concentrations of corncob liquid smoke, namely 0%, 2.5%, 5%, and 7.5% at a temperature of 40-50°C (1 hour), 50-60°C (1 hour), and 70-80°C (2 hours). The main parameter observed was amino acid profile, and supporting parameters were protein, water, phenol content, and organoleptic. The results show that amino acids in barracuda fish increased with increasing concentration of liquid smoke. The highest amino acid was generated by a 7.5% concentration of corncob liquid smoke with an essential amino acid value of lysine 22,035.56 mg/kg. Meanwhile, the highest non-essential amino acid was glutamic acid with a value of 36,868.31 mg/kg. The immediate concentration of 7.5% overall gave the best results with water content 48.11 ± 1.94%, protein content 25.43 ± 0.05%, phenol content 0.188 ± 0.00%, and organoleptic with a confidence interval of 8.367<μ<88.666.